Features of the SPINK5 gene polymorphism associations with food allergy onset and course in children - Pakholchuk, O. P.; Пахольчук, Ольга Петрівна (Запорізький державний медичний університет, 2015)
Resume. It is less known about role of the genetically predisposing factors in the onset and course of the food allergy (FA). We aimed to determine the association of the polymorphism in SPINK5 gene with FA. Materials and methods. DNA genotypes were identifi ed in children aged 2 months – 5 years of age with FA skin symptoms (n=53) depending on the presence of the guanine or adenine in both alleles in the 1258 position of the 14 th exzone. Results. Genomic frequencies of the SPINK5 polymorphism site were 15 (28.3%) for AA, 29 (54.7%) – AG, 9 (16.9%) – GG. Abnormal barrier gene STAT5 did not infl uence on the severity and kind of the FA symptoms, comorbidity. Children with AA<AG genotypes had signifi cantly higher prevalence of food immediate hypersensitivity (p<0.05). Conclusion. Not all food related skin manifestations are AD and small part of them are genetically predisposed. Роль генетичних факторів у розвитку та формуванні харчової алергії (ХА) залишається маловивченою. Мета роботи – встановити зв’язок поліморфізму гена SPINK5 із ХА. ДНК генотипи залежно від наявності гуаніну та аденіну в алелях у позиції 1258 14-го екзону визначили у 53 дітей у віці від 2 місяців і до 5 років. Генотип АА виявили в 15 (28,3%), AG – 29 (54,7%), GG – 9 (16,9%). SPINK5 генний поліморфізм не впливав на важкість і характер проявів ХА, коморбідність. Діти з AA<AG генотипом частіше мали харчову IgE-асоційовану сенситизацію (p<0,05). Встановили, що не всі симптоми, які пов’язані із вживанням їжі, – це АД, лише мала їх частина має генетичну детермінацію. Роль генетических факторов в развитии и течении пищевой аллергии (ПА) остается малоизученной. Цель работы – установить связь полиморфизма гена SPINK5 с ПА. ДНК генотипы в зависимости от наличия гуанина или аденина в аллелях в позиции 1258 14-го экзона определены у 53 детей в возрасте от 2 месяцев до 5 лет. Генотип АА был выявлен у 15 (28,3%), AG – 29 (54,7%), GG – 9 (16,9%). SPINK5 генный полиморфизм не влиял на тяжесть и характер проявлений ПА, коморбидность. Дети с AA<AG генотипом чаще имели пищевую IgE-ассоциированную сенситизацию (p<0,05). Установлено, что не все симптомы, связанные с пищей, – это АД, малая их часть генетически детерминирована.
Асоціація поліморфізму гена SPINK5 із формуванням і перебігом харчової алергії в дітей
Ассоциация полиморфизма гена SPINK5 с формированием и течением пищевой аллергии у детей
Keywords: Children; Food Allergy; SPINK5-Human Protein; Single Nucleotide Polymorphism; діти; харчова алергія; SPINK5; однонуклеотидний поліморфізм; дети; пищевая аллергия; SPINK5; однонуклеотидный полиморфизм